EFFECT OF SEED TUBER SIZE AND DATES OF HAULM KILLING ON GROWTH AND YIELD OF SEED POTATO CROP - Kumar, Vinod; Vyakarnahal, B. S.; Basavaraj, N. (Potato Journal, 2013)
An experiment using cv. Kufri Pukhraj was carried out for two years to study the effect of combinations of five seed tuber sizes (S1 - <20 g, S2 - 20-30 g, S3 - >30-40 g, S4 - >40-50 g and S5 - >50- 60 g) and four dates of haulm killing (D1 - 60, D2 - 70, D3 - 80 and D4 - 90 days after planting) on growth and yield of potato at Dharwad (Karnataka). Plant height, number of stems/hill, leaf area, plant dry matter, number and yield of tubers per plant were highest at S1 (>50-60 g) seed tuber size. These parameters recorded the lowest value at S1 (< 20 g) seed tuber size. Increase in seed size improved number of stems/hill and tuber yield per plant but decreased tuber yield per unit area. It also increased the proportion of large size tubers (> 50-60 g) and decreased the proportion of seed size tubers (>30-40 g). Haulm killing at 90 DAP recorded the maximum seed size and total tuber yield per plant and per hectare for all seed sizes used. The interactions were significant. Highest seed size and total tuber yield was obtained with the treatment combination of >30-40 g seed tuber size and haulm killing at 90 DAP. Other better treatment combinations were S3D3 (>30-40 g seed size and haulm killing at 80 DAP) and S4D4 (>40-50 g seed size and haulm killing at 90 DAP) while, significantly low yield was registered in >50-60 g seed tuber size and haulm killing at 90 days after planting.